Calculus for business, economics, and the social and life sciences - Hoffmann, Laurence D., 1943- (New York, NY : McGraw-Hill, 2013)
[This is a] text for students majoring in business, management, economics, or the life or social sciences. A prerequisite of two years of high school algebra is assumed. New exercises, new applications, and the addition of new technology supplements make [the text] a ... learning resource for students
Functions, graphs, and limits -- Differentiation : basic concepts -- Additional applications of the derivative -- Exponential and logarithmic functions -- Integration -- Additional topics in integration -- Calculus of several variables -- Appendix A: algebra review
Includes bibliographical references and indexes
Keywords: Calculus -- Textbooks; Textbooks; Textbooks